2012
DOI: 10.1074/jbc.m112.402958
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-induced IL-23p19 Subunit Is Regulated by cAMP-responsive Element-binding Protein and C/AATT Enhancer-binding Protein β in Bone Marrow-derived Dendritic Cells

Abstract: Background:The molecular mechanisms involved in IL-23 up-regulation by PGE2 are not elucidated. Results: PGE2 induces IL-23p19 through the EP4 cAMP-PKA/EPAC-CREB/C/EBP␤ signaling pathway. Conclusion: PGE2 synergizes with TLR ligands and with proinflammatory cytokines such as TNF␣ to up-regulate Il23a gene expression. Significance: Understanding is gained of one of the major functions of PGE2 leading to activation of pathogenic Th17 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 54 publications
2
33
0
7
Order By: Relevance
“…It is different than the recent report by the Ganea's group, which found in their BMDCs that PGE 2 amplifies LPS-induced Il23a expression by mobilizing both cAMP-PKA-CREB and cAMP-Epac-C/EBPb pathways. 25 Another difference between the studies is that Ganea's group consistently found that the PGE 2 action was exerted through both EP2 and EP4 receptors in their BMDCs, whereas our BMDCs utilize only EP4. As shown in the RESULTS section, our BMDCs expressed EP2 mRNA at a level comparable to EP4 but did not respond to an EP2 agonist that showed potent actions in T cells in an EP2-dependent manner.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is different than the recent report by the Ganea's group, which found in their BMDCs that PGE 2 amplifies LPS-induced Il23a expression by mobilizing both cAMP-PKA-CREB and cAMP-Epac-C/EBPb pathways. 25 Another difference between the studies is that Ganea's group consistently found that the PGE 2 action was exerted through both EP2 and EP4 receptors in their BMDCs, whereas our BMDCs utilize only EP4. As shown in the RESULTS section, our BMDCs expressed EP2 mRNA at a level comparable to EP4 but did not respond to an EP2 agonist that showed potent actions in T cells in an EP2-dependent manner.…”
Section: Discussionmentioning
confidence: 80%
“…This may have been because of mouse strain or preparation procedures; we used C57BL/6 mice as our source and Ganea's group used B10.A mice. 25 Previously, Nishigaki et al found different sensitivities of EP2 and EP4 to PGE 2 -induced desensitization. 27 Although that paper reported that EP4 undergoes desensitization more quickly than does EP2, which was the opposite of our finding, it showed that different sensitivities to desensitization do occur between EP2 and EP4.…”
Section: Discussionmentioning
confidence: 95%
“…The latter can be phosphorylated via EPAC. EPAC (via C/AATT enhancer-binding protein b) and phospho-CREB were shown to stimulate p19 transcriptional activity (22). Accordingly, we were able to show that a specific EPAC activator (8-CPT-2Me-cAMP) induced increased IL-23 production in LPS-DC (Supplemental Fig.…”
Section: Idc Express Functional B 2 Armentioning
confidence: 73%
“…However, the actual involvement of prostaglandin E 2 as an autocrine mediator has not been proved unambiguously. For instance, COX inhibition by a high concentration of indomethacin showed a weak inhibitory effect (7). A note of caution regarding the straightforward translation of the results on il23a transcription to the overall production of IL-23 arises from the possible influence of concomitant factors such as the parallel production of the IL-12/23 p40 chain and il23a mRNA stability (60).…”
Section: Discussionmentioning
confidence: 99%